PERUBAHAN SIFAT FISIK TANAH AKIBAT PEMBERIAN PUPUK KANDANG DAN MULSA PADA PERTANAMAN TERUNG UNGU (Solanum melongena L), ENTISOL, TONDO PALU - Abdul Kadir Paloloang, Ulfiyah A Rajamuddin, Ramli (AGROTEKBIS, 2016)
The abjective ofÂ the researah is to analysed Â to analysed changen physical ot Entisol tondo effected by giving of cage Â manure ane mulsa. To the porple eggplant. (melongena L solanum). This researe distriat of Â tond, palu city, the provinsi middle of Sulawesi. In February â mayÂ 2015 whicn have two factorials that were, the firs gave of mulsa (m1) compased by 2 level that were without of mulsa (mo) and used of mulsa (m1) Â estate farm, ail surfaces of land clossed or equivant 10 ton of ha-1 the second fautor with giving of cage manure lansist of 4 lefel ofÂ tteatawant and mthaut manure(control) that were ko=0 ton of ha-1,Â k1=10 ton of ha-1, k2=20 ton of ha-1, k3=30ton of ha 1 so that, obtaind 8x3=24 attempt.the resulf of researeh interaction (combination) of mulsa whit cage manure have an effeal real denatrring land in all of perception ofÂ variables,that were : Bulkdensity, land;ground aggregate, rate irrigate spacious capacities and land;ground porosity. The Dose fertilize cage counted 30 tons of ha-1 and giving of mulsa can influence denaturing of land;ground physical compared to other treatment.